Effective Analysis on Service Climate of Cooperative Banks in Rural Areas of Tamilnadu (International Journal of Scientific Research and Management (IJSRM), 2017)
Banking is a key industry in the service sector and it will not be travesty of truth to call it the financial nerve centre of the economy of a country. In the past, customers were simple persons and were happy at whatever banks dished out to them. Over a period with the competition and technological improvements, customers have become fully aware of their rights. This paper explains about the brief scrutiny of Indian banking industry would unearth the reasons behind the current scenario governed by the Banking Regulation Act of India 1949. A set of questionnaires were prepared, customers were selected randomly and were asked to respond their felt experience about the banks’ services while banking with the selected co-operative banks in rural areas. The primary data for the study are collected through questionnaires and personal interviews and secondary data collected from published reports, journals, research papers, fact sheets of the co-operative banks and different related sites from internet